1988
DOI: 10.1523/jneurosci.08-05-01728.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cytology and neuron-glial apposition of migrating cerebellar granule cells in vitro

Abstract: In developing mammalian brain, many neurons migrate to their final position by moving in direct apposition to radially oriented glial cells. Glial-guided migration can be visualized in microcultures of mouse cerebellar cells by the combined use of cellular antigen markers and high resolution time-lapse video microscopy (Hatten et al., 1984; Edmondson and Hatten, 1987). Such studies have demonstrated the behavior of migrating cells and revealed a motile leading process on the migrating neuron that resembles an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(145 citation statements)
references
References 24 publications
16
126
2
1
Order By: Relevance
“…In contrast, our imaging studies revealed nuclear migration past the centrosome, excluding the pulling effect of the centrosome as its major driving force. Our results are supported by previous electron microscopic observations that centrosomes are located to the side of cell bodies in migrating neurons (9,10). Studies using dissociated granule cells have indicated that small-amplitude movements of the soma (1.3 m on average) were preceded by centrosomal movements every 3-5 min (7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, our imaging studies revealed nuclear migration past the centrosome, excluding the pulling effect of the centrosome as its major driving force. Our results are supported by previous electron microscopic observations that centrosomes are located to the side of cell bodies in migrating neurons (9,10). Studies using dissociated granule cells have indicated that small-amplitude movements of the soma (1.3 m on average) were preceded by centrosomal movements every 3-5 min (7).…”
Section: Discussionsupporting
confidence: 91%
“…Instead, the centrosome is considered to play a key role in driving nuclear migration in neurons. The centrosome typically precedes and is coupled to the nucleus via perinuclear microtubules that envelop and capture the nucleus (6)(7)(8)(9)(10)(11). Current models suggest that the centrosome first moves into the leading process and serves as a cue for forward displacement of the nucleus along the microtubules (7,8,(12)(13)(14).…”
mentioning
confidence: 99%
“…During neuronal migration, the centrosome of the cell is uniformly positioned in front of the nucleus [63][64][65] , leading to a model in which the nucleus is translocated along microtubules in the "minus" direction through "minus"-end directed motors including dynein. Indeed, disruption of dynein function, or alterations in LIS1 or Ndel1, which are dynein components, similarly lead to alterations in this coupling, as measured by an increased distance between the nucleus and centrosome (i.e.…”
Section: Plays An Essential Role In Translocation Of the Nucleusmentioning
confidence: 99%
“…During migration, the Golgi, centrosome, and associated microtubule networks polarize the neuron in the direction of movement ( Fig. 3; Edmondson and Hatten 1987;Gregory et al 1988;Hatten 1999). Whereas the extending growth cone forms focal adhesions at the leading edge, migrating cells establish a broad interstitial junction beneath the cell soma (Gregory et al 1988).…”
Section: Polarity Proteins In Glial-guided Cns Migrationmentioning
confidence: 99%